2018
DOI: 10.3233/cbm-171040
|View full text |Cite
|
Sign up to set email alerts
|

Annexin A5 overexpression might suppress proliferation and metastasis of human uterine cervical carcinoma cells1

Abstract: ANXA5 overexpression in the uterine cervical carcinoma might play important roles in cell proliferation and metastasis of uterine cervical cancer cells and act as an anti-cancer gene in uterine cervical cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 33 publications
1
14
0
1
Order By: Relevance
“…Contrarily, large amounts of research demonstrated ANXA5 acts as tumor suppressor. For instance, ANXA5 can suppress cell proliferation and metastasis in uterine cervical carcinoma ( 13 ); it transfers to the mitochondria, suppressing the voltage-dependent anion channel (VDAC) oligomerization which leads to prostate cancer cell apoptosis ( 14 ). ANXA5 suppresses murine neuroblastoma cell proliferation by blotting PS which results in the enhanced T cell-dependent tumor immunity ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Contrarily, large amounts of research demonstrated ANXA5 acts as tumor suppressor. For instance, ANXA5 can suppress cell proliferation and metastasis in uterine cervical carcinoma ( 13 ); it transfers to the mitochondria, suppressing the voltage-dependent anion channel (VDAC) oligomerization which leads to prostate cancer cell apoptosis ( 14 ). ANXA5 suppresses murine neuroblastoma cell proliferation by blotting PS which results in the enhanced T cell-dependent tumor immunity ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…In support of this our speculation, Kang et al showed that the combined administration of metformin and Sorafenib significantly inhibits the recurrence and metastasis of primary liver cancer in HCC patients, after surgical resection [64]. Moreover, we observed that METF stimuli increased annexin A5 protein expression (Figure 6(c)): recent data indicate how the upregulation of this protein ameliorates antitumoral response, acting on cell cycle regulators [12, 13]. We speculated that METF, acting on annexin A5, could represent a novel coadjuvant in cancer therapy.…”
Section: Discussionsupporting
confidence: 83%
“…Molecular target therapy is now developing as a novel anticancer modality and seems to be a promising way for prolonging advanced HCC patient survival. Insulin-like growth factor (IGF) signaling is specifically required for hepatocyte malignant transformation and HCC progression [65, 66], especially the IGF-I receptor (IGF-IR) [13] and IGF-II expression in hepatocarcinogenesis [46, 65]. IGF-IR stimulates growth of HCC cells through the activation of the IGF-II/IGF-IR pathway: this receptor is not expressed in healthy mature hepatocytes, whereas HCC cells exhibit abnormal activation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Potential mechanisms for this include effects of ANXA5 on regulation of genes implicated in cell motility (including S100A4 , TIMP3 and RHOC ), 41 activation of PI3K–Akt–mammalian target of rapamycin signalling leading to tumour cell proliferation, 37 promotion of migration and invasion via upregulation of matrix metalloproteinases 2 and 9, 37 and effects on integrin signalling and mitogen‐activated protein kinase kinase–extracellular signal‐regulated kinase pathways 42 . Conversely, ANXA5 may have a protective role in some cancers because ANXA5 overexpression can inhibit proliferation and metastasis, including in uterine and cervical carcinoma cell lines 43 . In addition, administration of ANXA5 in a murine model of human papillomavirus 16‐associated cancer augmented antitumour immunity by binding to phosphatidylserine externalized by apoptotic tumour cells, which enhanced the immunogenicity of tumour antigens 44 …”
Section: Discussionmentioning
confidence: 99%